MELAWAN TEORI OTENTISITAS HADITS: (Counter Discourse Nabia Abbot Terhadap Teori Ignaz Goldziher) - Wathani, Syamsul (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2020)
In the scientific tradition, the study of Islam in the orientalisme is not stagnant, but has experienced development. This article focuses on the arguments of Nabia Abbot's argument and theory in refuting Goldziher's theory of the study of hadith. The author calls it a counter discourse. At least this article found three outlines of Nabia Abbot's rebuttal to Goldziher: (a) the theory of authenticity, Goldziher said the hadith was not an authentic report but a form of doctrinal reflection during the first two centuries after the prophet Muhammad. Abbot denies he views this view as wrong because it ignores historical evidence. For Abbot the hadith had appeared early in the century, as evidenced by the oral hadith of Muawwiyah (d. 60/680), Marwan (d. 65/684) and Abd Malik bin Marwan (d. 86/705). (b) Isnad's theory. Goldziher mentioned that the growth of the hadith in the third century Hijriyah was due to the history of history and the fabrication of the hadith. Nabia Abbott has argued with the argument that the number of hadiths is due to the growth of the hadith path in the geometric progression, not forgery. (c) Hadith Writing Theory, Goldziher said that the early hadith did not have a written reference, only oral, so the hadith in the form of thoughts could not be verified. Abbot denied, he said, that the beginning had been carried out in the narration and the modification of the hadith. Besides there are a number of books of hadith as in the text of Hammâm b. Munabbih (40-131 / 132 H).